Contribution of immune cells to bone metastasis pathogenesis - He, Ningning; Jiang, Jingting (Frontiers in Endocrinology, 2022)
Bone metastasis is closely related to the survival rate of cancer patients and reduces their quality of life. The bone marrow microenvironment contains a complex immune cell component with a local microenvironment that is conducive to tumor formation and growth. In this unique immune environment, a variety of immune cells, including T cells, natural killer cells, macrophages, dendritic cells, and myeloid-derived suppressor cells, participate in the process of bone metastasis. In this review, we will introduce the interactions between immune cells and cancer cells in the bone microenvironment, obtain the details of their contributions to the implications of bone metastasis, and discuss immunotherapeutic strategies targeting immune cells in cancer patients with bone metastasis.